Actio Communi Dividundo - I Wayan Suka Wirawan (Sociological Jurisprudence Journal, 2023)
The research article titled "Actio Communi Dividundo" delves into the intricate legal dynamics surrounding the sale-purchase of immovable property, particularly concerning land rights. In the event that the buyer is bound by marriage relationship, the rights to the land are the so-called joint rights (gono-gini) of a fair of husband/wife. However, regarding to the registration of their rights, PPAT generally does not register both husband and wive as the holders of the right or is registered only on the name of one holder of the right, without having to obtain consent from the other right holder. As a result, not all the name of the right holders is registered as the right holders. This situation is certainly detrimental to the party whose her name is not registered as the holder of the right, especially in the event of a divorce and the party who his name is registered are not willing to voluntarily share such joint property. This paper aims to show whether the practice of joint land (gono-gini) registration only on the name of one party without consent of the other party has been pursuant or instead contravene to legal principles. The method has been used is normative legal research, and it was found that the practice of registering joint land only on the name of one right holder without any consent of the other right holder is contrary to the principle that every legal act regarding to joint property must obtain the consent from the entire rights holders; a principle which historically based upon the Roman civil law tradition as contained in the Corpus Iuris Civilis and its transformation into Actio Communi Dividundo.